Resolution of pericardial effusion after minimally invasive surgical repair of pectus excavatum - Bostanci, Korkut; Ozyurtkan, Mehmet Oguzhan; Yuksel, Mustafa (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2014)
Pectus excavatum may cause the compression of the heart, thereby, disturbing the pericardial fluid turnover which results in pericardial effusion. In this article, we report a 32-year-old female case with pectus excavatum and chronic recurrent pericardial effusion. After the minimally invasive repair of pectus excavatum and pericardiocentesis, no recurrence was observed during one-year follow-up. By elevating the sternum and relieving the cardiac compression, minimally invasive repair of pectus excavatum may be helpful in restoring the pericardial fluid production and re-absorption mechanism.
Keywords: Minimally invasive surgery; pectus excavatum; carinatum; pericardium